Optical properties of Tl-doped Bi2Se3 single crystals - Janíček, Petr; Drašar, Čestmír; Krejčová, Anna; Lošťák, Petr; Navrátil, Jiří (Univerzita Pardubice, 2010)
Bi2–xTlxSe3 single crystals with the Tl content of cTl = 0 to 5.2×1024 atoms m–3 prepared from the elements of 5N purity by means of a modified Bridgman method were characterized by the measurements of infrared reflectance and transmittance. The values of the plasma resonance frequency Tp, optical relaxation time J, and high-frequency permittivity g4 were determined by fitting the reflectance spectra using plasma-resonance formula. It was found that the substitution of Tl atoms for Bi atoms in the Bi2Se3 crystal lattice leads to a decrease in the wp values implying a decrease in the free carrier concentration. This effect is explained within a model of the point defects in the crystal lattice of Bi2–xTlxSe3. The dependences of the absorption coefficient K on the energy of incident photons were determined from the transmittance spectra. The optical 76 Janíček P. et al./Sci. Pap. Univ. Pardubice Ser. A 16 (2010) 75–85 width of the energy gap decreases with the increasing Tl content. The values of the exponent $ from the relation of K ~ 8$ for the long-wavelength absorption edge range within the interval from 2.1 to 2.5 indicating the dominant scattering mechanism of free current carriers is the scattering on acoustic phonons.
Keywords: infrared reflectance; Bridgman method; transmittance